2023
DOI: 10.31577/cai_2023_1_157
|View full text |Cite
|
Sign up to set email alerts
|

Adding RLL Properties to Four CCSDS LDPC Codes without Increasing Their Redundancy

Abstract: This paper presents the construction of Run Length Limited (RLL) Error Control Codes (ECCs) from four Low Density Parity Check (LDPC) Codes specified by Consultative Committee for Space Data Systems (CCSDS). The obtained RLL-ECCs present a practical alternative to the CCSDS codes with pseudorandomizers. Their advantage is that the maximal runlengths of equal symbols in their codeword sequences are guaranteed, which is not the case if the common approach with pseudo-randomizers is used. The other advantages are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In [6] it was shown that RLL properties can be implemented into the standard codes [7] without additional redundancy and without the need to change the decoding procedures if some round conditions are valid [8]. The method is based on adding vectors called modifiers to encoded codewords with reordered symbols.…”
Section: Rll-ldpc Codes Obtained From Standard Ccsds-ldpsmentioning
confidence: 99%
See 4 more Smart Citations
“…In [6] it was shown that RLL properties can be implemented into the standard codes [7] without additional redundancy and without the need to change the decoding procedures if some round conditions are valid [8]. The method is based on adding vectors called modifiers to encoded codewords with reordered symbols.…”
Section: Rll-ldpc Codes Obtained From Standard Ccsds-ldpsmentioning
confidence: 99%
“…(2) GF and both will have length  . In (6) the index  denotes a key which is an element from a set  denoted as keyspace.…”
Section: Concept For Adding Lightweight Security To Three Rll-ldpc Ccdsmentioning
confidence: 99%
See 3 more Smart Citations